Bacteriological Quality of Drinking Water in Mardan, Khyber Pakhtunkhwa, Pakistan - Ali, Javid; Hassan, Said; Ziaurahman, Dr; Rahman, Inayat Ur; Abbas, Sadhair; Ullah, Sana (Ecoprint: An International Journal of Ecology, 2015)
The present study was aimed to isolate and identify micro-organisms load of drinking water of Mardan city, Khyber Pakhtunkhwa Pakistan. A total of 27 samples of drinking water were collected from different locations of the study area. Total Plate Count was determined by pour plate method, while total coliforms, total fecal coliforms and E. coli were determined by multiple tube fermentation method. Of the total collected samples, 17 (62.96%) samples were contaminated with either one or more than one type of microorganisms. The results of most probable number test showed that 13 (48.15%) samples were unsatisfactory. It was concluded that the water should be treated before consumption for drinking purpose. Regular assessment of the water quality is recommended as regular monitoring of the water quality for improvement not only prevents disease and hazards but also checks the water resources from becoming further polluted. ECOPRINT 21: 1-6, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11897